Hijaiyah Letter Learning Strategies to Improve Qur’an Reading Skills in Early Childhood at Anak Hebat (AHE) Kupu, Wanasari, Brebes - Nisfia, Ika Winayatun; Rizki, Haris Diar; Firmanda, Galih; Amin, Miftakhul; Sulistiono, Dwi; Ali, Mahtum (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
Introducing Hijaiyah letters is essential as the foundation for Qur’an reading skills, particularly for children aged 5–6 years, which is considered a golden age in their development. This study employs a qualitative approach with a case study design, involving observation, interviews, and documentation to collect data from teachers, parents, and children at the Anak Hebat (AHE) learning center. The findings reveal that AHE applies the AGA (Anak Surga) method, which incorporates titian ingatan (memory bridging) in the learning process. This method consists of six steps: brain gym, remedial, module reading, enrichment, writing, and educational games. Implementing this strategy has proven effective, as the children demonstrated significant improvement in recognizing letters, proper pronunciation, and reading short verses. Moreover, parental involvement in supporting learning at home also contributed to the success of the program. This study is expected to offer new insights into effective teaching strategies for non-formal educational institutions, especially in the context of Hijaiyah letter instruction.   Keywords: Learning Strategies, Hijaiyah Letters, Reading Skills, Early Childhood